2011
DOI: 10.1002/jcb.23163
|View full text |Cite
|
Sign up to set email alerts
|

Caspase‐2 deficiency protects mice from diabetes‐induced marrow adiposity

Abstract: Type I (T1) diabetes is an autoimmune and metabolic disease associated with bone loss. Bone formation and density are decreased in T1-diabetic mice. Correspondingly, the number of TUNEL positive, dying osteoblasts increases in bones of T1-diabetic mice. Moreover, two known mediators of osteoblast death, TNFα and ROS, are increased in T1-diabetic bone. TNFα and oxidative stress are known to activate caspase-2, a factor involved in the extrinsic apoptotic pathway. Therefore, we investigated the requirement of ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 61 publications
0
8
1
Order By: Relevance
“…These studies indicate a potential role for caspase-2 as a target in obesity, however, as with the other caspases, it is yet to be established if blocking caspase-2 can reverse pre-existing disease. Interestingly, Casp2 −/− mice have also been shown to be protected from streptozocin diabetes-induced bone marrow adiposity [73] suggesting depot-specific differences.…”
Section: Caspase-2 Function In Metabolic Diseasementioning
confidence: 99%
“…These studies indicate a potential role for caspase-2 as a target in obesity, however, as with the other caspases, it is yet to be established if blocking caspase-2 can reverse pre-existing disease. Interestingly, Casp2 −/− mice have also been shown to be protected from streptozocin diabetes-induced bone marrow adiposity [73] suggesting depot-specific differences.…”
Section: Caspase-2 Function In Metabolic Diseasementioning
confidence: 99%
“…Although T1DM and T2DM have clear differences in pathophysiology and consequences, we will discuss specific potential mechanisms for increased marrow fat in the two diseases here, noting when a potential mechanism applies to just one disease or is shared. We focus on possible causal mechanisms and acknowledge that there may be other factors at play not discussed in this review, including oxidative stress [42], adiponectin, glucocorticoids, and sex hormones.…”
Section: Potential Mechanism Of Increased Marrow Fat In Diabetesmentioning
confidence: 99%
“…A subsequent study showed that caspase-2 deficiency attenuated diabetes-induced bone marrow adiposity indicated by decreased PPARy, which is a marker for adipocyte differentiation, suggesting a potential role for caspsase-2 in adipocyte differentiation. 69 …”
Section: Caspase-2 In Cancer and Agingmentioning
confidence: 99%